Rotavirus vaccine impact assessment surveillance in India: protocol and methods. Issue 4 (25th April 2019) - Nair, Nayana P; Reddy N, Samarasimha; Giri, Sidhartha; Mohan, Venkata Raghava; Parashar, Umesh; Tate, Jacqueline; Shah, Minesh Pradyuman; Arora, Rashmi; Gupte, Mohan; Mehendale, Sanjay M; Kang, Gagandeep
Abstract : Introduction: Rotavirus infection accounts for 39% of under-five diarrhoeal deaths globally and 22% of these deaths occur in India. Introduction of rotavirus vaccine in a national immunisation programme is considered to be the most effective intervention in preventing severe rotavirus disease. In 2016, India introduced an indigenous rotavirus vaccine (Rotavac) into the Universal Immunisation Programme in a phased manner. This paper describes the protocol for surveillance to monitor the performance of rotavirus vaccine following its introduction into the routine childhood immunisation programme. Methods: An active surveillance system was established to identify acute gastroenteritis cases among children less than 5 years of age. For all children enrolled at sentinel sites, case reporting forms are completed and a copy of vaccination record and a stool specimen obtained. The forms and specimens are sent to the referral laboratory for data entry, analysis, testing and storage. Data from sentinel sites in states that have introduced rotavirus vaccine into their routine immunisation schedule will be used to determine rotavirus vaccine impact and effectiveness. Ethics and dissemination: The Institutional Review Board of Christian Medical College, Vellore, and all the site institutional ethics committees approved the project. Results will be disseminated in peer-reviewed journals and with stakeholders of the universal immunisation programme in India.